1993
DOI: 10.1148/radiology.189.1.8372222
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of the skin with 20-MHz US.

Abstract: The diagnostic role of high-frequency US appears limited. It did not help differentiate benign from malignant lesions, but it did enable accurate delineation of deep margins of lesions and allowed noninvasive measurement of thickness. These features may help in the preoperative evaluation of skin tumors and in monitoring the response to therapy for certain inflammatory conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(107 citation statements)
references
References 0 publications
2
102
0
3
Order By: Relevance
“…[11][12][13][14][15] It has also been shown that dermatologic diseases like systemic sclerosis and psoriasis, and also some therapeutic approaches such as radiotherapy, can alter skin thickness. 2,3,16 However, to our knowledge, our report is the first to focus on skin thickness over bony prominences among a wheelchair-user population.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15] It has also been shown that dermatologic diseases like systemic sclerosis and psoriasis, and also some therapeutic approaches such as radiotherapy, can alter skin thickness. 2,3,16 However, to our knowledge, our report is the first to focus on skin thickness over bony prominences among a wheelchair-user population.…”
Section: Discussionmentioning
confidence: 99%
“…There has also been a third factor, i.e. the technical factors limiting image resolution (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). It is often necessary to visualise sub-centimeter lesions or even smaller, as in the case when measuring the thickness of a melanoma, and this cannot be achieved using traditional 7-10 MHz ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…Conditions, which compromise this network, cause low echogenicity and reflect, for example, subepidermal increase of interstitial fluid in oedema. 13 High frequency ultrasound has been used in several skin diseases 14 but only in limited amounts in localised 15 and systemic scleroderma. [16][17][18][19] This report examines the performance of a standardised high frequency ultrasound protocol in longitudinal observations of patients with early phases of both types of SSc.…”
mentioning
confidence: 99%